Optimalisasi Tumbuh Kembang Balita melalui Stimulasi Sensory Play dan Program Isi Piringku Melalui Posyandu di Wedung, Demak - Cahyo Wulandari; Viviani Reta Tambunan; Dwi Lestari (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
Child nutrition and development issues remain a public health challenge. Similarly, Demak Regency still faces stunting issues. This condition can be influenced by parents' lack of understanding of balanced nutritional diets and appropriate developmental stimulation. To address these issues, the KKN PPM UGM Wedung Unit 2025 Team implemented a community service program in the form of Sensory Play Stimulation and Isi Piringku Socialization. This community service program aims to increase community understanding regarding the importance of growth and development stimulation and fulfilling balanced nutrition for toddlers. This program was implemented in Dukuh Tambak Gojoyo and Berahan Kulon Villages, Wedung District, Demak Regency. This program’s implementation involved 65 partisipants of mothers with toddlers, posyandu cadres, and PKK members as the main participants. The activity methods include interactive counseling, demonstrations of Isi Piringku preparation, and educational games using sensory play as a medium. The educational media used in the counseling include posters and leaflets. Pretests and posttests are conducted to measure participants' knowledge levels, both before and after socialization. The results of the activity showed an increase in parents' understanding of the Isi Piringku concept and the importance of early childhood developmental stimulation. This is evident from the improvement in posttest results which increased by 11.3% in Dukuh Tambak Gojoyo and 27.66% in Berahan Kulon Village. Furthermore, mothers and toddlers actively participated during the practical activities. Overall, this community service program has been implemented well and has the potential to be expanded to other regions to optimize child growth and development. With sufficient information available, parents are equipped to implement a balanced nutritional diet and appropriate developmental stimulation to support optimal child growth and development.